The development of a depressive disorder management model amongst Thai labours in the Eastern Economic Corridor (ECC) - Sorut Wongsuttitum; Boonyapa Pokasem; Chaweerat Chernchomkul (Archives of Depression and Anxiety - Peertechz Publications, 2024)
Depression is a barrier to the human workforce. However, the lack of major policies and guidelines for depression disorder in Thailand hinders healthcare workers from addressing this issue. Therefore, this research examines ways to develop depressive disorders in laborers. This study used a qualitative approach to examine the context of depression management in labor. The results of this study presented factors related to depression management from individual to organizational contexts. This finding suggests that stakeholders should take the first step of depression prevention outside healthcare services.